HAK MENGUASAI NEGARA DI BIDANG PERTAMBANGAN MINERAL DAN BATUBARA DI ERA OTODA - Muchamad Taufiq (JOURNAL EQUITABLE, 2023)
The economy is structured as a joint venture based on the principle of kinship", the meaning is profound, namely that the economic system developed gotong royong. The inherent meaning of people's economic rights to be maintained by the State Ruled Rights. Law Number 3 of 2020, Article 92 provides authority in the form of rights for mining license (IUP) and special mining business permit (IUPK) holders. This arrangement is a form of freedom to trade these mining materials so that it has the potential to obscure the constitutional right of the state, so that the state's position becomes a sub-ordination of business actors. The spirit of regional autonomy is essential to provide flexibility to maximize mineral and coal mining management. The results: the economic rights of the people are attached to the meaning of the right to be controlled by the state is a manifestation of the fulfillment of the economic rights of the people as a subject to obtain prosperity. The regulation that gives the permission holder authority over minerals and coal to possess is legally contrary to the constitution.